Long non‐coding RNA linc01433 promotes migration and invasion in non‐small cell lung cancer. Issue 5 (13th March 2018) - Qian, Banglun; Wang, Xiang; Mao, Chao; Jiang, Yiqun; Shi, Ying; Chen, Ling; Liu, Shuang; Wang, Bin; Pan, Shu; Tao, Yongguang; Shi, Hongcan
Abstract : Background: For many years, lung cancer has been the most common and deadly cancer worldwide. Early diagnosis of non‐small cell lung cancer (NSCLC) in particular is very difficult because the symptoms are often ignored. The five‐year survival rate is very low despite great improvements to therapy. Thus, there is an urgent need to identify prognostic biomarkers and target molecules for the clinical diagnosis and individualized treatment of NSCLC. Methods: We performed quantitative real‐time PCR to determine the expression levels of the long non‐coding RNA (lncRNA) linc01433 in NSCLC and normal matched lung tissue. Subsequently, we established cell lines with overexpression or knockdown of linc01433 to evaluate the effects on proliferation and metastasis in vitro. Epithelial‐to‐mesenchymal transition was examined using Western blot. Results: Linc01433 was significantly overexpressed in NSCLC tissues compared to normal lung tissues. In addition, linc01433 levels were associated with smoking history. Linc01433 overexpression in lung cancer cells increased proliferation, migration, and invasion abilities, as well as epithelial‐to‐mesenchymal transition. Conclusions: Linc01433 is a cancer‐related lncRNA that may have an oncogene‐like effect in NSCLC.